2003
DOI: 10.1111/j.1473-2130.2004.00098.x
|View full text |Cite
|
Sign up to set email alerts
|

Pemphigus can be induced by topical phenol as well as by foods and drugs that contain phenols or thiols

Abstract: Pemphigus is an autoimmune disease that results from the interaction between predisposing genetic factors and exogenous factors, the most common environmental factors being drugs and food. Topical phenol has induced pemphigus in one patient. Drugs and foods that induce pemphigus are divided into three main groups according to their chemical structure: thiols (containing a sulfhydryl group), phenol, nonthiol nonphenol. Thiol and phenol compounds can induce acantholysis in tissue cultures in vitro. The suggested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 33 publications
(49 reference statements)
0
17
0
1
Order By: Relevance
“…It was suggested that several factors, such as phenols or thiols, may induce acantholysis and trigger auto-immune pemphigus [23]. Organophosphate pesticides were shown to block the acetylcholinesterase channel [24].…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that several factors, such as phenols or thiols, may induce acantholysis and trigger auto-immune pemphigus [23]. Organophosphate pesticides were shown to block the acetylcholinesterase channel [24].…”
Section: Discussionmentioning
confidence: 99%
“…Phenol derivatives were reported to induce acantholysis both in vitro and in vivo , after topical application and consumption [24, 40, 41]. The role of polyphenolic compounds – tannins, contained in food or water, was suggested in research articles and case reports describing fogo selvagem (“wild fire”) endemic PF [4145].…”
Section: Discussion Of the Issue Of Pemphigus Triggering In Relation mentioning
confidence: 99%
“…Thiol compounds or mercaptans cause acantholysis in vivo and in vitro in cultured tissues [20, 40, 55]. Thiol-mediated cell-cell adhesion loss seem to be caused by direct biochemical aberration of desmosome structure itself, e.g.…”
Section: Discussion Of the Issue Of Pemphigus Triggering In Relation mentioning
confidence: 99%
“…15 On üç pemfiguslu hasta üzerinde yapılan bir çalışmada 12 hastanın hastalık ortaya çıkmadan önceki bir yıl içinde stresli yaşam olaylarına maruz kaldığı gösterilmiştir. 16 Bizim çalışmamızda kontrol grubu ile yapılan karşılaştırma sonucunda bazı stresli olayların hasta grubunda istastistiksel olarak anlamlı ölçüde (p<0,01) yüksek oranda yaşandığı tespit edildi. Hastaların beslenme alışkanlıklarını araştırmaya yönelik, çay, kahve, acı ve baharatlı yiyecek yeme alışkanlıkları sorgulandığında, her iki grupta da çayın fazla miktarda tüketildiği, acı ve baharatlı yiyeceklerin az oranda yenildiği görüldü.…”
Section: Discussionunclassified